Mechanical properties of a hybrid cemented carbide composite - Deng, Xin; Patterson, B.R; Chawla, K.K; Koopman, M.C; Fang, Z; Lockwood, G; Griffo, A (International journal of refractory metals & hard materials, 2001)
Microstructural effects on the mechanical properties of a hybrid metal matrix composite, double cemented (DC) carbide, have been investigated. DC carbide contains granules of WC/Co cemented carbide in a matrix of cobalt. Overall composite hardness increases with decreased granule cobalt content as well as with decreased intergranular matrix fraction of cobalt. High-stress abrasive wear resistance also increases with decreased granule cobalt content and matrix fraction. Fracture toughness of the composite increases with increased cobalt matrix fraction and to a lesser extent with increased granule cobalt content. Increased granule size increases both fracture toughness and wear resistance. DC carbide exhibits a superior combination of fracture toughness and high-stress wear resistance than conventional cemented carbide. The combination of toughness and wear resistance in the composite improves with increased granule hardness.